2004
DOI: 10.1074/jbc.m402924200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Phosphoinositide 3-Kinase γ, Rac, and PAK Signaling in Chemokine-induced Macrophage Migration

Abstract: In macrophages, chemotactic stimuli cause the activation of Rac and PAK, but little is known about the signaling pathways involved and their role in chemotactic gradient sensing. Herein, we report that in macrophages, the chemokine RANTES (regulated on activation normal T cell expressed and secreted)/CCL5 activates the small GTPase Rac and its downstream target PAK2 within seconds. This response depends on G i activation and largely on the subsequent triggering of phosphoinositide 3-kinase ␥ (PI3K␥) and Rac. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 65 publications
5
65
1
Order By: Relevance
“…Therefore, based on our previous and present findings, it may be speculated that the Gab1, p115 RhoGEF, Rac1, and RhoA signaling may be diverging at Pak1/2 levels in the modulation of HASMC versus THP-1 cell migration in response to thrombin (17). A role for Pak2 in macrophage migration has also been demonstrated previously (54). Furthermore, the activation of Pak2 by heterotrimeric G proteins and the adaptor protein NCK may indicate that several signaling events influence Pak2 in the mediation of cell migration (55).…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, based on our previous and present findings, it may be speculated that the Gab1, p115 RhoGEF, Rac1, and RhoA signaling may be diverging at Pak1/2 levels in the modulation of HASMC versus THP-1 cell migration in response to thrombin (17). A role for Pak2 in macrophage migration has also been demonstrated previously (54). Furthermore, the activation of Pak2 by heterotrimeric G proteins and the adaptor protein NCK may indicate that several signaling events influence Pak2 in the mediation of cell migration (55).…”
Section: Discussionmentioning
confidence: 82%
“…Our data showing reduced Rac1 activity in mutant BMDMs suggest that impaired PIP3 polarization was caused by alteration of the positive feed back loop that involves Rac/PI3K reciprocal activation (37). In mouse macrophages, PI3K␥ deficiency does not affect Rac2 and only halves Rac1 activity (22), thus indicating that PI3K␥ only partially contributes to chemoattractant-mediated Rac activation. Our results are in agreement with a role of PIP3 in controlling the duration rather than the triggering of Rac activity (7) and suggest an involvement of PI3K in mediating GAP activation in response to chemoattractants.…”
Section: Discussionmentioning
confidence: 80%
“…Downstream of PI3K, the small GTPase Rac is a major player in cell spreading, polarization and leading edge formation (5,22). Analysis by pull-down assay of Rac1 activity induced by C5a showed that in wild-type cells, Rac-GTP rapidly increased, peaked at 1 min and declined within 5 min (Fig.…”
Section: Constitutive and Delocalized Pip3 Production Impairs Leadingmentioning
confidence: 99%
“…Although Ga i1 is primarily found in the brain, Ga i2 and Ga i3 are abundantly expressed in the immune system. Many biological functions of leukocytes, including macrophage phagocytosis and migration, involve Ga i -mediated signaling (11,12). Previous studies in mice lacking Ga i2 or Ga i3 suggested key roles of these two G i isoforms in distinct cellular responses (13)(14)(15)(16).…”
mentioning
confidence: 99%